Selection into Self-Improvement and Competition Pay: Gender, Stereotypes, and Earnings Volatility - Klinowski-Gomez, D (Elsevier B.V., 2019)
We examine whether men and women differ in their willingness to select into a contract that pays upon improving one s past performance. Experiment participants choose to perform a task under either a regular piece rate, or a larger piece rate provided they improve relative to a previous round. Women are less willing than men to select into self-improvement pay, and this gender gap is largely explained by higher risk aversion and (to a smaller extent) lower self-confidence. High earnings volatility widens the gender gap, and makes self-improvement pay less attractive than competition pay. We find no effect of gender stereotypes in the willingness to sort into self-improvement. The results provide insight into the feasibility and potential of using self-improvement contracts as gender-neutral incentive mechanisms. © 2018